Legal perspectives on the Russia-Ukraine War : international and polish approaches - Balcerzak, Micha??; Ca??a-Wacinkiewicz, Ewelina (Routledge, 2025)
"This book critically examines the legal ramifications of Russia's invasion of Ukraine, and the aftermath of these events. Combining international and domestic perspectives, it synthesises nearly three years of legal responses to the aggression. Russia's aggression against Ukraine has triggered profound legal challenges with far-reaching implications for the states directly involved, third parties, and the international legal order. This book offers a comprehensive analysis of the international and domestic legal dimensions of the conflict. Beginning by exploring the international legal framework, including assessing the responses of the United Nations system and key legal issues arising from the war. Exploring topics such as human rights, international humanitarian law, and the law of war, the book also analyses Poland's response to the war, discussing the legislative and policy measures undertaken to address the impact of the crisis. Poland, Ukraine's immediate neighbour, has played a pivotal role in managing the unprecedented influx of Ukrainian refugees and adapting its legal framework to the challenges posed by the war. The book uses Poland as a lens through which to examine the international legal response. This book will be of interest to researchers in the field of international law and human rights law"-- Provided by publisher.
Keywords: War (International law); International law and human rights.; Humanitarian law.; Humanitarian law -- Poland.; Aggression (International law); Russian Invasion of Ukraine, 2022.; Russo-Ukrainian War, 2014-; Ukraine -- Foreign relations -- Russia (Federation); Russia (Federation) -- Foreign relations -- Ukraine.; elektronické knihy; electronic books